2021
DOI: 10.1016/j.arth.2020.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Modern Internet Search Analytics and Total Joint Arthroplasty: What Are Patients Asking and Reading Online?

Abstract: Introduction Patients considering total joint arthroplasty often search for information online regarding surgery, however little is known about the specific topics that patients search for and the nature of the information provided. Google compiles frequently asked questions associated with a search term using machine learning and natural language processing. Links to individual websites are provided to answer each question. Analysis of this data may help improve understanding of patient concerns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 41 publications
5
110
1
Order By: Relevance
“…Regarding surgeon proficiency, it can be considered that spending extra time to explain the diagnosis or treatment of a patient's condition may alleviate their feelings of dissatisfaction. A recent study by Shen et al found that the most common questions searched on the internet regarding total joint arthroplasty pertained to arthritis management, rehabilitation, and patients' ability to perform specific tasks [18]. Addressing these topics with patients may potentially improve satisfaction and alleviate surgeon-dependent complaints pertaining to bedside manner or surgeon proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgeon proficiency, it can be considered that spending extra time to explain the diagnosis or treatment of a patient's condition may alleviate their feelings of dissatisfaction. A recent study by Shen et al found that the most common questions searched on the internet regarding total joint arthroplasty pertained to arthritis management, rehabilitation, and patients' ability to perform specific tasks [18]. Addressing these topics with patients may potentially improve satisfaction and alleviate surgeon-dependent complaints pertaining to bedside manner or surgeon proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Linked answers to each FAQ reveal which information sources individuals are likely to encounter when searching Google for medical information. Our methodology was adapted from a study by Shen et al [ 21 ], who used Google FAQs to reliably reveal common concerns about orthopedic procedures and to assess the transparency of the suggested information.…”
Section: Methodsmentioning
confidence: 99%
“…By expanding the tab on a FAQ, additional FAQs appear. We repeated this process until reaching a minimum of 150 FAQs for each search, as studies using similar methodology have recommended using 50-150 sources [ 21 ]. We used the high end of the recommended number of sources (150) for two reasons: to increase the likelihood of encountering an FAQ that would be pertinent to the current study and to reflect the precedent set in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, ours is the first study of its kind which analyzes the online resources Indian patients utilize to approach an orthopedic surgeon before undergoing total knee replacement. Few other studies like Shen et al, 16 Fraval et al, 5 Meneghini et al 17 and Carlin et al 18 have analyzed the trends of the internet usage by the orthopedic outpatients. In the current study, seventy percent (32% patients themselves and 38% relatives) of our patients searched information on internet about TKR before approaching the surgeon for getting the procedure done.…”
Section: Discussionmentioning
confidence: 99%